Brain Aggregates: An Effective In Vitro Cell Culture System Modeling Neurodegenerative Diseases. Issue 3 (5th February 2016) - Ahn, Misol; Kalume, Franck; Pitstick, Rose; Oehler, Abby; Carlson, George; DeArmond, Stephen J.
Abstract: Drug discovery for neurodegenerative diseases is particularly challenging because of the discrepancies in drug effects between in vitro and in vivo studies. These discrepancies occur in part because current cell culture systems used for drug screening have many limitations. First, few cell culture systems accurately model human aging or neurodegenerative diseases. Second, drug efficacy may differ between dividing and stationary cells, the latter resembling nondividing neurons in the CNS. Brain aggregates (BrnAggs) derived from embryonic day 15 gestation mouse embryos may represent neuropathogenic processes in prion disease and reflect in vivo drug efficacy. Here, we report a new method for the production of BrnAggs suitable for drug screening and suggest that BrnAggs can model additional neurological diseases such as tauopathies. We also report a functional assay with BrnAggs by measuring electrophysiological activities. Our data suggest that BrnAggs could serve as an effective in vitro cell culture system for drug discovery for neurodegenerative diseases.